Dimensioning and Modeling of a Circular Inductor Integrated in a Boost Converter - Y. Benhadda; A. Hamid; T. Lebey (Журнал нано- та електронної фізики)
This paper presents the dimensioning and modeling of a circular inductor integrated in a Boost micro converter. At first, we define the characteristics of the Boost micro converter, which is the starting point for the design our component, taking into account the electrical and magnetic characteristics of the materials selected. The second, a Boost micro converter schematic simulation coupled with ideal and integrated inductor was presented. This conceptual model of the Boost is best understood in terms of the relation between voltage and current of the inductor. Finely, we have simulated the electromagnetic effects in integrated inductor in the air, and with substrate using the finite element method.